MODEL PROBLEM BASED LEARNING (PBL) BAHAN KIMIA DALAM MAKANAN UNTUK MENUMBUHKAN POLA MAKAN SEHAT - Mulia Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
The  research  is  conducted  based  on  high  number  of  intoxication  at  school  due  to  student’s  low understanding  on  the  negative  effects  of  additives  substance  in  food.  Therefore  it  is  needed  a learning  models  that  can  improve  the  understanding  of  additives  substance  in  food.  The formulation  of  the  problem  posed  is  effectiveness  this  models  to  improve  student  learning outcomes and to foster healthy eating. The purpose of the study is to analyze the effect of problem- based learning towards the refinement of cognitive learning outcomes and to foster healthy eating. This reseach conducted on class VIII SMPN 1 Kota Tegal consists of two classes taken at random from  the  seven  classes,  one  class  as  a  control  group  and  another  as  an  experimental  group.  The PBL models is effective showed by students who learning mastery > 85%, and positive effect on students' perception of healthy eating by 97,47%. Data correlation on cognitive learning outcomes and  students'  positive  perceptions  of  healthy  eating  show  at  0,689  with  significance  value  of 0,01<0,05 which means the instructional model of PBL can foster healthy eating in students.   Key words: chemical substances in food, healthy eating, problem based learning